PENGARUH PENGARUH FASILITAS, PELAYANAN DAN SAPTA PESONA TERHADAP KEPUASAN WISATAWAN DI KIKI BEACH RESORT BATAM - Fakhriani, Hanifah Malya; Firnanda, Aura Azzura Poetri; Putri, Ariqah Syahirah; Arini, Ainun; Rafiffalah, Muhammad Adelio; Alexandro, Andhika Glenn (Pusat Penelitian dan Pengabdian Kepada Masyarakat Politeknik Pariwisata Bali, 2025)
This study was conducted to explore the level of tourist satisfaction at Kiki Beach Resort Batam. This tourist destination offers the natural beauty of the beach, a variety of water activities, and comfortable lodging facilities. Tourist satisfaction is an important thing that must be considered by the manager. This satisfaction is influenced by the quality of services and facilities provided. With the increasing number of domestic and international tourists to Batam, expectations for service quality are also getting higher. This research also emphasizes the importance of applying the Sapta Pesona concept to create a safe, clean, and comfortable tourist environment. It is expected that the research results can provide data-based recommendations to improve the quality of services and facilities, as well as encourage innovation in the development of tourism products. Therefore, Kiki Beach Resort can continue to compete in the tourism industry and attract more tourists, both domestic and international, and support the growth of tourism in Batam. This research is expected to provide new insights into the potential development of Kiki Beach Resort as a leading destination. In addition, it serves as a reference for academics and practitioners in the